Gymnema sylvestre for diabetics - Singh, Vinay Kumar; Umar, Shahid; Ansari, Shamim Akhtar; Iqbal, Muhammad (Journal of herbs, spices & medicinal plants, 2008)
Gymnema sylvestre R.Br., a medicinal plant that is indigenous to India, grows wild in the tropical forests of central, western and southern parts of India and in the tropical areas of Africa, Australia, and China. The plant is listed in the Indian pharmaceutical codex and is popular in Indian systems of traditional medicine, such as Sidha, Unani, and Ayurveda, where the plant leaves are used to treat type II (adult-onset) diabetes (Madhumeha). Due to a lack of successful agrotechniques, however, the plant has become vulnerable and therefore, the different varieties and populations growing in various phytogeographical regions merit attention of the research community. This article elucidates the botany, biochemistry, pharmacology, and medicinal uses of the plant and suggests a strategy for conservation of the species while emphasizing the need for further research.